Investigation of some factors influence on the work of extra pure hydrogen generator - Glazunov, G.P.; Konotopskiy, A.L.; Vinogradov, D.M.; Bondarenko, M.N.; Maznichenko, S.M.; Svynarenko, O.P. (Вопросы атомной науки и техники, 2017)
The developed models of ultra-pure hydrogen generators had been designed, produced and tested. The influence of membrane temperature and form, position in the flame, installation of additional screens etc. were investigated. The special device, so called hydrogen compremator (accumulator-compressor), was designed, produced and investigated. Its function is to accumulate low pressure pure hydrogen flow (pressure is less than 1 Torr) from generator and to convert it to high hydrogen pressure of about 15 atm in the compremator volume. The combined work of hydrogen generator and compremators was investigated. Hydrogen generator and compremator were tested in the regime of pure hydrogen puffing in plasma device DSM-1, providing the required parameters during experiment on the examine of metal erosion. The examines had shown capacity for work of both hydrogen generator and compremator in the conditions of real plasma physical experiments.